Non-destructive analyses of Late Roman and Byzantine glasses from ancient Sicily: Methodological challenges and measurable results. (December 2018) - Gueli, A.M.; Pasquale, S.; Tanasi, D.; Hassam, S.; Garro, V.; Lemasson, Q.; Moignard, B.; Pacheco, C.; Pichon, L.; Stella, G.; Politi, G.
Highlights: The glasses are Soda-Lime-Glass of the Imperial Roman and Byzantine periods. The glass production methodology is uniform all along the considered period. Burial conditions produced a strong de-alkalization and network dissolution. Colored glasses present typical chromophores. Glass from the Catacombs of St. Lucy belong to the HIMT and Levantine type group. Abstract: The study of glassmaking and glass trade in the Mediterranean region represents one of the most intriguing topics for Late Roman and Early Medieval archaeology. Until a decade ago, the identification of production centers and distribution patterns was mainly based on typological features and coloring of glass vessels. The growing popularity in the application of archaeometric techniques for characterization and study of archaeological artifacts has revolutionized the field of ancient glass studies. However, the critical lack of primary data and the limited use of analytical methods to determine the provenance of such materials has generated a gap in the knowledge, especially in important regions such as Sicily. The evidence emerged from two recent fieldworks brought the opportunity to test non-destructive techniques on an assemblage of ancient vessels to compare Late Roman and Early Medieval glass production technology and emphasizes evidence of continuity and discontinuity.